Consumer Health Informatics Interventions Must Support User Workflows, Be Easy-To-Use, and Improve Cognition: Applying the SEIPS 2.0 Model to Evaluate Patients' and Clinicians' Experiences with the CONDUIT-HID Intervention. Issue 4 (3rd April 2017) - Martinez, Vanessa I.; Marquard, Jenna L.; Saver, Barry; Garber, Lawrence; Preusse, Peggy
ABSTRACT: The aim of this research was to gain a holistic understanding of patients' and clinicians' experiences with the CONDUIT-HID (CONtrolling Disease Using Inexpensive Technology—Hypertension In Diabetes) intervention, intended to be a technology-enabled consumer health informatics (CHI) approach to control hypertension. We examined patients' experiences utilizing the technologies to share patient blood pressure data with their care team via a qualitative analysis of patient ( n = 21) and clinician ( n = 5) interviews. Using the SEIPS 2.0 sociotechnical systems model, our evaluation revealed that minimizing usability issues and supporting participant workflow were important—but not sufficient—for CHI intervention success. The ability of the CHI intervention to support the cognitive development of patients' self-management skills and to facilitate strategic collaboration among care team members was also important. These insights can provide CHI and the human–computer interaction (HCI) communities with a framework of generalizable findings to better design future CHI interventions.